Effects of lesions of the human posterior thalamus on ocular fixation during voluntary and visually triggered saccades. Issue 11 (15th October 2004) - Rafal, R; McGrath, M; Machado, L; Hindle, J
Abstract : Objective: To investigate the role of the posterior thalamus in controlling voluntary and visually triggered eye movements and ocular fixation. Methods: The latency to initiate saccades to peripheral targets (visually triggered) and in response to verbal commands (voluntary) was measured in three patients with unilateral lesions of the posterior thalamus, in normal controls, and in neurological controls with Parkinson's disease. On half the trials a fixation point offset simultaneously with target onset, and on half it remained visible. Results: Offset of the fixation point simultaneous with target onset decreased saccade latency for both voluntary and visually triggered eye movements in controls, but only for voluntary saccades in patients with thalamic lesions. Conclusions: These findings suggest that separate neural systems control fixation when making voluntary and visually triggered eye movements, and that the thalamus is involved in the control of fixation for visually triggered but not for voluntary saccades.